Pierre Fauchard: the father of dentistry - Castro-N., Jaime A. (Revista Facultad de Odontología Universidad de Antioquia, 2018)
This paper presents a short biografy about the dental surgeon Fierre Fauchard. Likewise, this article shows vital aspects about the father of dentistry. The purpouse of this article is to show to the students and the persons who are interested in the subject a wide vision about the work of Fauchard.